KONTROL DIRI DAN PERSEPSI TERHADAP IKLIM SEKOLAH DENGAN PERILAKU BULLYING PADA SISWA - Fiki Febrian Dwi Prasetya (Pascasarjana IAIN Sorong, 2022)
The rise of bullying cases in schools is very worrying, especially for victims who often receive bullying committed by their own friends. Individuals who often receive bullying at school experience a number of psychological disorders such as anxiety, loneliness, feeling worthless and feeling unacceptable by their peers. Each individual has a mechanism that can help regulate and direct behavior called self-control. The purpose of this study was to determine the relationship between self-control and perceptions of school climate with bullying behavior. Subjects totaled 205 junior high school (SMP) students, sampling using purposive sampling technique. The data collection method used is a Likert scale instrument which has been tested for validity and reliability with Cronbach's Alpha coefficient of self-control 0.904, school climate 0.949 and bullying behavior 0.961. The data obtained were analyzed using regression analysis. The results showed that there was a relationship between self-control and perceptions of school climate with bullying behavior, the F value was 121.059 (p <0.01), so the third hypothesis was accepted. The effective contribution of self-control and school climate perceptions to predict bullying behavior in students was 54.5%, while the remaining 45.5% was influenced by other factors which were not examined in this study. This research is expected to be useful in knowing what predictors are the factors that have a relationship with bullying behavior, so that it can be used as a reference for taking intervention actions to reduce bullying behavior in students